Zinc in Plants Current Knowledge and Recent Advances - Tripathi D. Phil., Durgesh Kumar; Tripathi D. Phil., Durgesh Kumar; Singh, Vijay Pratap; Pandey, Sangeeta (Academic Press, 2024)
Zinc in Plants: Current Knowledge and Recent Advances addresses zinc hunger, the transport of zinc in the soil-plant interphase, zinc and abiotic stress in plants, and zinc and plant disease. Written by experts in the field, this title is an essential resource to all scientists and students interested in plant physiology, biochemistry and agriculture. During their life, plants encounter various challenges, including their normal development under changing environmental conditions. Zinc (Zn) is an essential component of thousands of proteins in plants, although it is toxic in excess, and is essential for many processes throughout the plant lifecycle. - Provides an overview on the origin, chemistry and behavior of zinc in soil - Discusses zinc deficiency and toxicity along with causes and remediation - Presents the latest advances in zinc signaling, regulation and genotypic variation